The Optimum Conditions of Carboxymethyl Chitosan Synthesis on Drug Delivery Application and Its Release of Kinetics Study - Parsaoran Siahaan; Nadira Cahyaning Mentari; Ustera Octovindra Wiedyanto; Dwi Hudiyanti; Suci Zulaikha Hildayani; Marlyn Dian Laksitorini (Indonesian Journal of Chemistry, 2017)
In this paper, carboxymethyl chitosan (CMC) was synthesized and studied as a carrier to encapsulate vitamin (as drug model) and controlled release. Chitosan (CS) is a polycationic derivated from chitin, which suitable for active substance carrier system on biomedical function. CS has good properties such as non-toxic, biodegradable, and biocompatible. However, CS insoluble in an aqueous solvent so CS was modified chemically into CMC. CMC was formed by reacting CS and monochloroacetic acid with sodium hydroxide (NaOH) as a catalyst. Optimation was performed by varying the NaOH concentration during alkalizing the CS and the temperature reaction. The functional group and crystallinity of CS and CMC were estimated by FTIR and XRD. The degree substitution of carboxymethylation has an average value of 0.60. The results show optimum temperature reaction and NaOH concentration were 60 °C and 40% (w/v). The nicotinamide (NA), a hydrophilic vitamin, was loaded within CMC matrix system through in vitro precipitation method. To confirm the encapsulation of NA in CMC and the release kinetics of NA from CMC in distilled water was studied through UV-Vis spectrophotometry. The release profile of NA from CMC matrix system carried out for 3 h and 12 h. The rate of NA release from CMC increases with increasing time and the follows a zero order, Higuchi, and Korsmeyer-Peppas kinetics rules.